Development of Problem-Based Learning Student Worksheet Integrated with Ethnoscience on Acid-Base Material - Emmilya Febri Marthin; Hardeli; Budhi Oktavia; Desy Kurniawati (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop problem-based learning student worksheets integrated with ethnoscience on acid-base materials that are valid and practical. This research uses a development research method (Research and Development) with a 4-D model. The data of this study were collected through validity sheets completed by 4 validators, namely 2 chemistry lecturers and 2 chemistry teachers, and with a practicality questionnaire sheet completed by 2 chemistry teachers and by 35 students of SMAN 1 Batusangkar as respondents. Data were analyzed using quantitative descriptive method, using Aiken’s V. The result for content validity is 0.88 and construct validity is 0.90 with valid category. The result for teachers practicality is 0.95 and students practicality is 0.82 with practical category. Based on the results of the research that has been conducted, it can be concluded that the development of problem-based learning-based student worksheets integrated with ethnoscience on acid-base material is valid and practical.